Water Resource Research at the School of Geographic Sciences of the National University: An Overview of the Main Results of Water Balances in the Micro-Watersheds of the Central Region of Costa Rica - Hernando Echeverría, Ligia; A. Orozco-Montoya, Ricardo (Revista Geográfica de América Central., 2024)
In Costa Rica, although water resources are abundant, certain areas face difficulties due to reduced availability for residents, leading to issues in supplying water for domestic and industrial use. The School of Geographic Sciences has actively addressed this issue. Since 2001, it has been quantifying water resources through the calculation of water balances in the micro-watersheds of the Poás, Ciruelas, Segundo, Bermúdez, Tibás, and Pará rivers. These studies have determined that the predominant availability is moderate, which suggests that it will soon become low. Therefore, it is urgent to implement proper management of the micro-watersheds to mitigate excessive water use.